PENERAPAN PRINSIP AKUNTANSI SYARIAH DALAM PERBANKAN SYARIAH - Arif Zairifli, Ahmad Izul; Latifah, Eny (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
Islamic banking is a financial sector that operates in accordance with Islamic sharia principles. These principles prohibit usury (interest) and activities that are contrary to Islamic law. Islamic Accounting is an accounting system that adheres to the principles of Islamic sharia. These principles aim to create transparency, fairness, and compliance with Islamic law in all financial transactions. Islamic Banking is one of the economic sectors that apply Islamic accounting principles. Islamic accounting principles have an important role in regulating Islamic banking operations. This article outlines the application of Islamic accounting principles in the context of Islamic banking. The application of Islamic accounting principles in Islamic banking involves a number of principles namely Islamic accounting emphasizes the avoidance of riba (interest) and gharar (uncertainty) in financial transactions. This creates fairness and eliminates speculative elements in Islamic banking business.